A participatory Ecohealth study of smallholder pig system in upland and lowland of Lao PDR - Khamlome, Boualam; Inthavong, Phouth; Phimphachanhvongsod, V.; Donnelly, B.; Blaszak, Kate; Gilbert, Jeffrey (2011)
Objective: To conduct baseline seroprevalence surveys of pig key zoonoses and evaluate public health risks of pig-raising & pork consumption in one upland and one lowland province, Lao PDR. Methodology: Baseline seroprevalence surveys were conducted in two provinces, Louangphrabang representative of ‘upland’ and Savannaket province for ‘lowland’. The selection of villages is based on the village human population data available from the 2005 National census and GIS data. The statistical programme was used to randomly select 30 villages weighted by human population for each Province. Per village, the village chief was interviewed to obtain general information about each village and fifteen pigs were randomly sampled and smallholder owners interviewed. Simultaneously 15 villagers were randomly selected, interviewed and blood sampled. The training and field activities done with integrated transdisciplinary approaches for district and provincial staff. Human and pigs tests for exposure to Taenia/Cysticercosis, Trichinellosis, Hepatitis E virus and Japanese encephalitis virus (Also in pigs: Erysipelas, CSF, FMD and PRRS). Result: Preliminary (unadjusted) seroprevalence results for the upland province have been determined while lowland results are pending. Statistical analysis will be undertaken to ascertain disease prevalence and provide indication of associated risks for zoonoses, production and environmental impacts with associated data from the questionnaires. Using Survet and MySQL programme on power calculation of 80%, 95% CI. P-values less than 0.05 will be considered to be statistically significant. Outputs: Baseline seroprevalence surveys & results of risk factor evaluation will assist with improvement of pig and human health by reducing risks of pig related zoonoses for farmers, villagers, consumers, traders and slaughterhouse workers. It is anticipated that this will guide future intervention studies and policy.